The Impact of The Problem-Based Learning Model on The Mathematical Problem-Solving Skills of Students - Meisari, Elawita; Herpratiwi; Oktaria , Sheren Dwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on the mathematical problem-solving ability of fifth-grade students at SD Negeri 3 Balerejo, Central Lampung. The research method used was a quasi-experimental design with a non-equivalent control group design. The study involved 60 students divided into two groups: an experimental class that used the PBL model and a control class that used conventional learning methods. The research instrument was an essay test on mathematical problem-solving ability. The data analysis results showed a significant difference between the mathematical problem-solving abilities of students taught using the PBL model and those taught using conventional methods. Thus, the PBL model has a positive effect on improving elementary school students’ mathematical problem-solving abilities.